2013
DOI: 10.1017/jfm.2013.608
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of motile elongated micro-organisms in turbulence

Abstract: We study the effect of turbulence on marine life by performing numerical simulations of motile microorganisms, modelled as prolate spheroids, in isotropic homogeneous turbulence. We show that the clustering and patchiness observed in laminar flows, linear shear and vortex flows, are significantly reduced in a three-dimensional turbulent flow mainly because of the complex topology; elongated micro-orgamisms show some level of clustering in the case of swimmers without any preferential alignment whereas spherica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 27 publications
5
91
1
Order By: Relevance
“…Apparently, the tendency to cluster is less strong, indicating the variation in response to changes in the flow field due to the importance of the orientation. Very recently, a similar reduction of clustering has been reported for motile prolate-shaped micro-organisms (Zhan et al 2014). Although these organisms are not heavier than the fluid and do not settle due to gravity, they nevertheless cross the streamlines of the fluid by swimming.…”
Section: Resultssupporting
confidence: 69%
“…Apparently, the tendency to cluster is less strong, indicating the variation in response to changes in the flow field due to the importance of the orientation. Very recently, a similar reduction of clustering has been reported for motile prolate-shaped micro-organisms (Zhan et al 2014). Although these organisms are not heavier than the fluid and do not settle due to gravity, they nevertheless cross the streamlines of the fluid by swimming.…”
Section: Resultssupporting
confidence: 69%
“…A prerequisite in this context is that the swimming cells are bottom heavy (like P. reticulatum) and thereby are able to orient themselves by a balance between viscous and gravitational torque (Pedley & Kessler 1992, Karimi & Ardekani 2013, Zhan et al 2014. The viscous torque is due to the vertical shear force formed between the dense falling plume and the upwards swimming cells.…”
Section: Role Of Bioconvection and Gyrotaxis In Vertical Migrationmentioning
confidence: 99%
“…Bioconvection and fluid mechanics theory have been applied to explain such phenomena (Pedley & Kessler 1992, Vincent & Hill 1996, Ghorai & Hill 2005, 2008, Karimi & Ardekani 2013, Zhan et al 2014, and gyrotaxis is considered to be the main regulatory mechanism for upwardsswimming cells (Kessler 1985, Mitchell et al 1990. Bioconvection therefore describes a type of convection set up by density instability at the surface due to dense cell aggregations formed by upwardsswimming microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…For elongated microswimmers, their flow-driven motion always involves the Jeffery orbit [42]. Recent studies have revealed how their aggregations are affected by different flow types and their motilities in response to possible external stimuli [43][44][45][46], i.e., gyrotaxis, chemotaxis, phototaxis, and so on. All these studies demonstrate that the Jeffery orbit dynamics is a fundamental aspect of the motion of anisotropic objects in viscous flows.…”
Section: Introductionmentioning
confidence: 99%